1997
DOI: 10.1021/jo961920w
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Functionalized Tropanes by Rhodium(II) Carboxylate-Catalyzed Decomposition of Vinyldiazomethanes in the Presence of Pyrroles

Abstract: A series of enantiomerically enriched tropanes was synthesized by the rhodium(II) octanoatecatalyzed reaction of various N-BOC-protected pyrroles with vinyldiazomethanes. The overall 3 + 4 annulation occurs by a tandem cyclopropanation/Cope rearrangement. Asymmetric induction was best achieved in these transformations by using either (S)-lactate or (R)-pantolactone as a chiral auxiliary on the vinyldiazomethanes. Reactions carried out with the chiral catalyst tetrakis-[N-(4-tert-butylbenzenesulfonyl)-(L)-proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 42 publications
3
86
0
2
Order By: Relevance
“…Similar results have been reported before. 13 These results imply that neither could the major rotamer be arbitrarily affiliated to the anti rotamer nor could the minor rotamer be arbitrarily affiliated to the syn rotamer. It is vital -prior to determining the absolute configuration -not to neglect the key step of distinguishing the major and minor rotamers carefully for identifying the syn and anti forms.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar results have been reported before. 13 These results imply that neither could the major rotamer be arbitrarily affiliated to the anti rotamer nor could the minor rotamer be arbitrarily affiliated to the syn rotamer. It is vital -prior to determining the absolute configuration -not to neglect the key step of distinguishing the major and minor rotamers carefully for identifying the syn and anti forms.…”
Section: Resultsmentioning
confidence: 93%
“…Both methoxy signals of the two rotamers at υ 3.85 and 3.68 ppm appear as quartets (J D 1.59 Hz) because of the long-distance coupling with the CF 3 group. For the major rotamer of compound 2 (2 major ), we started with the assignment of the C-3 chemical shift by 1 H- 13 C HMQC and DEPT135 so that the chemical shift of H-3 was easily determined. Thereby, and assisted by 1 H-1 H COSY and 1 H, 1 H coupling constant information (Table 2), the signals of the protons at C-2, C-4, C-5 and C-6 could be identified unambiguously, including their stereochemical positions (axial and equatorial).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] However, Davies et al reported in 1997 the synthesis of tropanes by a rhodium-catalyzed [4 + 3] cycloaddition between a chiral vinyl diazoacetate and N-Boc-pyrrole. [14] This reaction was later exploited during the asymmetric synthesis of tropanes by the same group as well as by Riché and co-workers. [15,16] Even though this process might not be scalable, it held promise as an easy and quick route to key intermediate 4.…”
Section: Resultsmentioning
confidence: 99%
“…These reports now include diastereomeric excesses of up to 97% in the dirhodium(II) octanoate catalysed cyclopropanation of styrenes and vinyl ethers with (R)-pantolactone-and (S)-lactate-substituted vinyldiazomethane 18 with (Table 1) (Davies et al, 1993c(Davies et al, , 1997a These workers (Davies et al, 1998a) have shown that appropriate choice of vinyldiazo substituent allows facile subsequent transformation of the cyclopropyl products to 2,3-dihydrofurans with high asymmetric induction. This methodology has been extended to diene systems, furans (Davies et al, 1996b) to give 8-oxabicyclo[3.2.1]octan-3-ones and pyrroles (Davies et al, 1997b) to give tropanes (Scheme 4).The fundamental reaction sequence has allowed the preparation of the oxabicycles 20-22 and a series of 2β-acyl-3β-aryltropanes 23 (Davies et al, 1994a(Davies et al, , 1996c CCOO, as in catalysts 6 (substituents varied from H, Me, and Ph; to OH, NHAc, and CF 3 ) and Kennedy et al (1990) persued the chiral prolinate derivatives 7 (Z = H). They found that enantioselectivities in the cyclopropanation of styrene with ethyl diazoacetate were less than 12% ee and 30% ee respectively.…”
Section: Intermolecular Processesmentioning
confidence: 99%